A type III-B CRISPR-Cas effector complex mediating massive target DNA destruction. Issue 4 (16th December 2016) - Han, Wenyuan; Li, Yingjun; Deng, Ling; Feng, Mingxia; Peng, Wenfang; Hallstrøm, Søren; Zhang, Jing; Peng, Nan; Liang, Yun Xiang; White, Malcolm F.; She, Qunxin
Abstract: The CRISPR (clustered regularly interspaced short palindromic repeats) system protects archaea and bacteria by eliminating nucleic acid invaders in a crRNA-guided manner. The Sulfolobus islandicus type III-B Cmr–α system targets invading nucleic acid at both RNA and DNA levels and DNA targeting relies on the directional transcription of the protospacer in vivo . To gain further insight into the involved mechanism, we purified a native effector complex of III-B Cmr–α from S. islandicus and characterized it in vitro . Cmr–α cleaved RNAs complementary to crRNA present in the complex and its ssDNA destruction activity was activated by target RNA. The ssDNA cleavage required mismatches between the 5΄-tag of crRNA and the 3΄-flanking region of target RNA. An invader plasmid assay showed that mutation either in the histidine-aspartate acid (HD) domain (a quadruple mutation) or in the GGDD motif of the Cmr–2α protein resulted in attenuation of the DNA interference in vivo . However, double mutation of the HD motif only abolished the DNase activity in vitro . Furthermore, the activated Cmr–α binary complex functioned as a highly active DNase to destroy a large excess DNA substrate, which could provide a powerful means to rapidly degrade replicating viral DNA.